Columbia, Democracy, and the Intermingling Thereof - Will Clifft (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
Since it began in the 1960s, much has been said and written about the various layers and aspects of the conflict in Colombia. Beginning as a civil war, this ongoing struggle has evolved from a struggle between peasant groups fighting to recapture their land from a powerful class of agro-elites to include multiple local and international actors with such diverse motivations as philosophical ideals, capital gain, and the execution of international, sociopolitical power plays. To better understand the gravity of the modern-day situation in Colombia and to attempt to ascertain how and why this decades-long struggle may be finally drawing to a close, I briefly explore the history of the conflict and review the ways in which the principal actors have directly influenced the development of the social and political infrastructure of this country. By analyzing past trends in this conflict and comparing them to current actions of guerrilla groups, the Colombian government, and international actors, I explain why it is reasonable to believe that this bloody chapter of Colombia’s history may be nearing a conclusion even if its memory will be etched into the minds of the generations to come.